MEMBIASAKAN TRADISI AGAMA: ARAH BARU PENGEMBANGAN PENDIDIKAN AGAMA ISLAM DAN BUDI PEKERTI DI SMA NEGERI 3 YOGYAKARTA - Moch Fuad (Department of Islamic Education, The State Islamic University Sunan Kalijaga Yogyakarta, 2017)
This study was aimed to describe: (1) the learning process of PAI based on the culture and character of the nation in SMA Negeri 3 Yogyakarta, (2) the reform of model and contextualization of the material (integrated domain) by PAI teacher, (3) reveals the model reformation and material contextualization (Integrated domain) conducted by PAI teachers can improve the domain of knowledge, attitudes and behavior of students, (4) the practice of practicing the students in school and at home. Research on